Job Satisfaction as a Mediator of Abilities and Rotation on Performance in Educational Personnel Faculty of Law, Brawijaya University, Malang - SHOLIKHAH, Mar’atun; HADIYATI, Ernani; HALIM, Abdul (PT Keberlanjutan Strategis Indonesia, 2023)
Performance is the work results of an employee or group of employees during a specific period that are compared with the performance standards determined by the company. Many variables influence this, including workability, job rotation, and job satisfaction. This research aims to test and analyze the influence of 1) workability on performance, 2) work rotation on performance, 3) workability on job satisfaction, 4) work rotation on job satisfaction, 5) job satisfaction on performance, 6) workability on performance through job satisfaction, 7) work rotation on performance through job satisfaction. This research was conducted at the Faculty of Law, Brawijaya University, Malang, using an explanatory research approach with a saturated sampling technique, obtaining 74 educational staff. Data was collected using a questionnaire method given directly to respondents. Then, it was analyzed using path analysis. The results prove that all the proposed hypotheses are accepted, namely:1) workability influences performance, 2) work rotation influences performance, 3) workability influences job satisfaction, 4) work rotation influences job satisfaction, 5) job satisfaction influences performance, 6) workability influences performance through job satisfaction, 7) work rotation affects performance through job satisfaction.